Application of Malay Traditional Architecture Elements as Regional Identity towards Sustainable City - Hidayat, Wahyu (RUAS, 2011)
Development of a sustainable city is a complex process with interactions of numerous aspects such as economic, environment, and social in urban living. Architecture is a major part in creating identity or character of the city and influencing quality of life of city community. In the context of architecture and urban design, sustainable architecture can be achieved if cultural aspects and ecological aspects are synergized as two connected entities. The study aims to identify and to analyse the application of Malay traditional architecture elements in contemporary buildings design in Pekanbaru. The assessment is based on two variables which are cultural aspect that shows application of Malay traditional architecture character as regional identity and ecological aspect that reflects application of Malay traditional architecture elements to respond the climatic condition. This research use qualitative methodology to analyse form and character of the buildings in term of application of Malay traditional architecture elements, and quantitative methodology is used with descriptive analysis to analyse the level of application of Malay traditional architecture elements in different categories and analysis. The research identifies that majority of contemporary building design use Malay traditional architecture elements improperly according to the philosophy of Malay traditional culture. The application of Malay traditional architecture character tends to show regional identity in the building design compared to respond ecological considerations. This study also identifies the different result between government buildings and private buildings in the application of Malay traditional architecture elements. The findings indicate the inconsistency of government policy enforcement in building permission to preserve the identity of Malay culture for the improvement of quality of life in Pekanbaru.Keywords: Malay traditional architecture elements, regional identity, sustainable city